Heat-killed Akkermansia muciniphila ameliorates allergic airway inflammation in mice - Yoon, Seol Ah; Lim, Younggap; Byeon, Hye Rim; Jung, Jiyeon; Ma, Seongho; Hong, Moon-Gi; Kim, Dohak; Song, Eun-Ji; Nam, Young-Do; Seo, Jae-Gu; Lee, Sang-Nam (Frontiers in Microbiology, 2024)
Allergic asthma (AA) is a common inflammatory airway disease characterized by increased airway hyper-responsiveness (AHR), inflammation, and remodeling. Akkermansia muciniphila is a strictly anaerobic bacterium residing in the gut and is a promising next-generation probiotic to improve metabolic inflammatory syndrome. A recent study suggested the beneficial effect of live A. muciniphila on allergic airway inflammation (AAI) in mice. However, whether the heat-killed form can improve AAI requires further investigation. Mice sensitized and challenged with house dust mites (HDM) develop AA hallmarks including inflammatory cell infiltration, goblet cell hyperplasia, and subepithelial collagen deposition in the lungs. These phenomena were reversed by oral administration of the heat-killed A. muciniphila strain EB-AMDK19 (AMDK19-HK) isolated from the feces of healthy Koreans. Furthermore, AMDK19-HK diminished the HDM-induced AHR to inhaled methacholine, lung mast cell accumulation, and serum HDM-specific IgE levels. It also led to the overall suppression of IL-4, IL-13, and eotaxin production in bronchoalveolar lavage fluids, and Il4, Il5, Il13, and Ccl17 gene expression in lung tissues. Moreover, AMDK19-HK suppressed Th2-associated cytokine production in the splenocytes of HDM-sensitized mice in vitro. Additionally, a combination of 16S rRNA gene sequencing and short-chain fatty acid (SCFA) analysis in cecal samples revealed that AMDK19-HK modulated the relative abundance of circulating SCFA-associated gut genera, including a positive correlation with Lachnospiraceae_ NK4A136_group and a negative correlation with Lachnoclostridium and significantly increased cecal SCFA concentrations. Finally, AMDK19-HK improved intestinal mucosal barrier function. These results suggest that the oral administration of AMDK19-HK ameliorates HDM-induced AAI in mice by suppressing Th2-mediated immune responses and could have a protective effect against AA development. Muc2, Zo-1, Ocln, and Cldn1 genes in the colon were measured by RT-qPCR. Expression levels were normalized to the housekeeping gene Gapdh and were expressed as a relative ratio. Data are expressed as mean ± SEM from a representative experiment of 3 performed (n = 5 mice per group). ns, not significant. * P < 0.05, ** P < 0.01, **** P < 0.